2013
DOI: 10.1080/10503307.2012.717310
|View full text |Cite
|
Sign up to set email alerts
|

Self-compassion and fear of self-compassion interact to predict response to eating disorders treatment: A preliminary investigation

Abstract: Gilbert (2005) proposed that the capacity for self-compassion is integral to overcoming shame and psychopathology. We tested this model among 74 individuals with an eating disorder admitted to specialized treatment. Participants completed measures assessing self-compassion, fear of self-compassion, shame, and eating disorder symptoms at admission and every 3 weeks during treatment. At baseline, lower self-compassion and higher fear of self-compassion were associated with more shame and eating disorder patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 43 publications
6
89
1
7
Order By: Relevance
“…It would be interesting to know whether these persistently low levels of self-compassion contribute to the poorer outcomes AN patients tend to experience during and after treatment for their eating disorder. Indeed, there is growing evidence that deficits in self-compassion are associated with more severe and prolonged eating disorder pathology in eating disorder patients [45]. …”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to know whether these persistently low levels of self-compassion contribute to the poorer outcomes AN patients tend to experience during and after treatment for their eating disorder. Indeed, there is growing evidence that deficits in self-compassion are associated with more severe and prolonged eating disorder pathology in eating disorder patients [45]. …”
Section: Discussionmentioning
confidence: 99%
“…The 2-week self-compassionate letter-writing intervention appeared to be acceptable, feasible, and efficacious. a p < .10; *p < .05; **p < .01; ***p < .001. have more severe symptoms and poorer treatment outcomes (Kelly et al, 2013(Kelly et al, , 2014. These numbers are quite remarkable given that roughly half the sample did not self-identify as having an eating disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results suggest that over 2 weeks, working on the development of self-compassion may help these individuals feel less ashamed and more open to, and capable of, self-compassion, all of which have been associated with reduced eating pathology over time (Kelly et al, 2013(Kelly et al, , 2014. Preliminary results suggest that over 2 weeks, working on the development of self-compassion may help these individuals feel less ashamed and more open to, and capable of, self-compassion, all of which have been associated with reduced eating pathology over time (Kelly et al, 2013(Kelly et al, , 2014.…”
Section: Limitations Future Research and Conclusionmentioning
confidence: 98%
See 1 more Smart Citation
“…A preliminary investigation showed that low self-compassionate individuals with higher fear of self-compassion presented more shame and ED pathology [107].…”
Section: Self-compassionmentioning
confidence: 99%